Small RNA profiling reveals the involvement of microRNA-mediated gene regulation in response to symbiosis in raspberry - Yang, Zhiyu; Yuan, Lianmei; Zhu, Haifeng; Jiang, Jing; Yang, Hongyi; Li, Lili (Frontiers in Microbiology, 2022)
Dark septate endophytes (DSEs) can form reciprocal symbioses with most terrestrial plants, providing them with mineral nutrients in exchange for photosynthetic products. Although the mechanism of plant-DSEs is well understood at the transcriptional level, little is known about their post-transcriptional regulation, and microRNAs (miRNAs) for the symbiotic process of DSE infestation of raspberry have not been identified. In this study, we comprehensively identified the miRNAs of DSE-infested raspberry symbiosis using Illumina sequencing. A total of 361 known miRNAs and 95 novel miRNAs were identified in the roots. Similar to other dicotyledons, most of the identified raspberry miRNAs were 21 nt in length. Thirty-seven miRNAs were differentially expressed during colonization after inoculation with Phialocephala fortinii F5, suggesting a possible role for these miRNAs in the symbiotic process. Notably, two miRNAs (miR171h and miR396) previously reported to be responsive to symbiotic processes in alfalfa also had altered expression during raspberry symbiosis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses suggests that miRNAs are mainly involved in regulatory mechanisms, such as biological processes, cellular metabolic processes, biosynthesis of secondary metabolites, plant–pathogen interactions, and phytohormone signaling pathways. This study revealed the potential conservation of miRNA-mediated post-transcriptional regulation in symbiotic processes among plants and provides some novel miRNAs for understanding the regulatory mechanisms of DSE–raspberry symbiosis.